2022
DOI: 10.3389/fphar.2022.883445
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Exosomes-Mediated Transfer of hsa-miR-320a Overcomes Chemoresistance in Cervical Cancer Cells via Targeting MCL1

Abstract: In cervical cancer (CC), cisplatin resistance greatly restricts the application in clinical. Here, we report that engineered exosomes-mediated transfer of hsa-miR-320a overcomes chemoresistance in cervical cancer cells via targeting Myeloid Cell Leukemia Sequence 1 (MCL1). In DDP resistant CC tissues, as well as cell lines, it was found that miR-320a expression is lower, engineered miR-320a exosomes were used to attenuate DDP resistance in Hela/DDP and Caski/DDP cells. Mechanistically, we find that MCL1, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Exosomes derived from miR-221-3p mimic-transfected CC cells promoted invasion, migration, and angiogenesis of CC cells through downregulation of MAPK10 116 and lymphangiogenesis and lymphatic metastasis of HLECs by targeting VASH1 117 . miR-320a expression was decreased in CC tissues, and engineered miR-320a exosomes enhanced the chemoresistance and tumor growth by targeting MCL1 118 .…”
Section: Exosomes In CCmentioning
confidence: 98%
“…Exosomes derived from miR-221-3p mimic-transfected CC cells promoted invasion, migration, and angiogenesis of CC cells through downregulation of MAPK10 116 and lymphangiogenesis and lymphatic metastasis of HLECs by targeting VASH1 117 . miR-320a expression was decreased in CC tissues, and engineered miR-320a exosomes enhanced the chemoresistance and tumor growth by targeting MCL1 118 .…”
Section: Exosomes In CCmentioning
confidence: 98%
“…Zhou et al found that miR-320a expression was low in cisplatin-resistant CC. Myeloid Cell Leukemia Sequence 1, a cisplatin-resistant molecule, was regulated by engineered miR-320a EVs, thereby reducing resistance to cisplatin therapy in CC [ 74 ].…”
Section: Progress In the Treatment Of Evs In CCmentioning
confidence: 99%